2014
DOI: 10.1186/1471-2407-14-448
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic MicroRNAs: miR-155, miR-19a, miR-181b, and miR-24 enable monitoring of early breast cancer in serum

Abstract: BackgroundMicroRNAs (miRs) represent a distinct class of posttranscriptional modulators of gene expression with remarkable stability in sera. Several miRs are oncogenic (oncomiRs) and are deregulated in the pathogenesis of breast cancer and function to inhibit tumor suppressors. Routine blood monitoring of these circulating tumor-derived products could be of significant benefit to the diagnosis and relapse detection of early-stage breast cancer (EBC) patients.MethodsAim of this project was to determine express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
128
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(134 citation statements)
references
References 20 publications
5
128
1
Order By: Relevance
“…miRNA-155 (miR-155) is one of the miRNAs that are overexpressed in multiple cancers, as demonstrated in numerous studies (17). In gastric cancer cells, the level of miR-155 has been reported as significantly increased, and the overexpression of miR-155 promoted cell proliferation and invasion, while silencing miR-155 inhibited cell proliferation and enhanced apoptosis (18). A similar phenomenon was observed in lung cancer cells.…”
Section: Introductionmentioning
confidence: 63%
“…miRNA-155 (miR-155) is one of the miRNAs that are overexpressed in multiple cancers, as demonstrated in numerous studies (17). In gastric cancer cells, the level of miR-155 has been reported as significantly increased, and the overexpression of miR-155 promoted cell proliferation and invasion, while silencing miR-155 inhibited cell proliferation and enhanced apoptosis (18). A similar phenomenon was observed in lung cancer cells.…”
Section: Introductionmentioning
confidence: 63%
“…In silico analysis of publicly available datasets also showed that high miR-155 levels associated with poor prognosis on tamoxifen. Several studies have reported that miR-155 levels could be monitored in patients' blood samples, and that this miRNA is differentially expressed in breast cancer patients when compared with healthy women (26,51,52). Therefore, our results highlight a potential diagnostic approach and therapeutic intervention based on miR-155 patient stratification.…”
Section: Discussionmentioning
confidence: 82%
“…Furthermore, it was mirrored that decreased miR‐181b restrained vascular remodelling by activating TGF‐β/pSmadD2/3 pathway,40 and addition of angiotensin II into cardiac fibroblasts could significantly down‐regulate miR‐181b expression 41. In addition, it has been illuminated that miR‐181b might suppress breast cancer cells’ capacity of metastasis by targeting CXCL1 and CXCL2, a couple of inflammatory cytokines 42, 43, 44. He et al45 arrived at conclusions that miR‐181b was highly expressed with prostate cancer tissues and cell line (ie.…”
Section: Discussionmentioning
confidence: 99%